Affiliative social tuning reduces the activation of prejudice. (March 2016) - Huntsinger, Jeffrey R.; Sinclair, Stacey; Kenrick, Andreana C.; Ray, Cara
Past research on affiliative social tuning has shown that individuals who experience affiliative motivation toward another person come to exhibit implicit prejudice consistent with the apparent beliefs of that person. The present research seeks to elucidate the mechanism by which such malleability occurs. Is it interpersonally cued cognitive control, consistent with dual-process models of prejudice regulation, or a contextual change in automatic associations, consistent with shared reality theory? QUAD modeling of participants' responses revealed that affiliative social tuning of implicit prejudice was solely a function of changing associations (Studies 1–3). Furthermore, instructions to try to inhibit prejudice within a particular interpersonal context did not yield implicit attitude change (Study 2).